INVESTIGATING ON STUDENTS’ SELF CONFIDENCE IN SPEAKING SKILLS OF EFL LEARNERS - Pangestu, Aditya Dwi; Martriwati, Martriwati (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to analyze the self-confidence of speaking English Language Education students at Muhammadiyah Prof. Dr. Hamka. This study uses Quantitative to determine the level and factors of students' self-confidence. The instrument used for data collection is closed questionnaires by the Sugiyono method. The results of this study found that the level of self-confidence in speaking skills is high, and the factors of self-confidence are Optimistic attitude and Potential and adequate abilities.